Biclonal gammopathy of undetermined significance in a patient with systemic lupus erythematosus and antiphospholipid syndrome - V. Bruzzese; P. Scolieri; J. Pepe (PAGEPress Publications, 2022)
The case of a patient suffering from systemic lupus erythematosus with associated antiphospholipid antibody syndrome is described. In this patient, on protein electrophoresis, two monoclonal immunoglobulin G λ and k peaks were seen, defining a condition of biclonal gammopathy of undetermined significance (BGUS). This condition is extremely rare, especially in chronic inflammatory rheumatic diseases. The criteria of a BGUS are defined. We also underline how this condition can be the expression of a concomitant unrecognized cancer, a possible amyloidosis or an infectious process.